(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article contains ideas on ensuring the rational use of water for the needs of the population and economic sectors, preventing pollution and depletion, protecting the rights and legitimate interests of citizens, improving legal liability, protecting the environment, liability for damage to the environment and water resources, environmental problems, and an analysis of the impact measures used for environmental violations in foreign countries.